2021
DOI: 10.1155/2021/4832864
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Data Splitting on Performance of Machine Learning Models in Prediction of Shear Strength of Soil

Abstract: The main objective of this study is to evaluate and compare the performance of different machine learning (ML) algorithms, namely, Artificial Neural Network (ANN), Extreme Learning Machine (ELM), and Boosting Trees (Boosted) algorithms, considering the influence of various training to testing ratios in predicting the soil shear strength, one of the most critical geotechnical engineering properties in civil engineering design and construction. For this aim, a database of 538 soil samples collected from the Long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 322 publications
(165 citation statements)
references
References 95 publications
0
107
0
1
Order By: Relevance
“…In this study, we have followed the influence of data Splitting performance (Nguyen et al, 2021) to divided the entire dataset was splitting into 70:30 ratio. Some of the field photographs in this study area are shown in Figure 3.…”
Section: Ls Inventory Mapmentioning
confidence: 99%
“…In this study, we have followed the influence of data Splitting performance (Nguyen et al, 2021) to divided the entire dataset was splitting into 70:30 ratio. Some of the field photographs in this study area are shown in Figure 3.…”
Section: Ls Inventory Mapmentioning
confidence: 99%
“…The training process was carried out with the amount of data as much as 70% of the dataset, while testing was carried out with 30% of the data from the dataset ( Nguyen et al, 2021 ). Both the training and testing processes for each topology were repeated ten times by varying the initial weight values.…”
Section: Methodsmentioning
confidence: 99%
“…In [5], Nguyen Q. et al have evaluated and compared the performance of different machine learning models, such as artificial neural network, extreme learning machine, and boosting trees (Boosted) models, considering the influence of various training to testing ratios in predicting the soil shear strength. Although the researchers are environmental engineers, they have done a great job in their investigation by dividing the datasets into training and testing datasets to assess the models' performance.…”
Section: Related Workmentioning
confidence: 99%